Parasitismo por Monogenoidea em Piaractus mesopotamicus (Characiformes, Characidae) cultivados no rio Paraná (Brasil) - Leão, M. S.L.; Justo, M. C.N.; Bueno, G. W. [UNESP]; Cohen, S. C.; São Clemente, S. C. (FapUNIFESP (SciELO), 2017)
This study investigated the occurrence, prevalence, mean abundance and mean intensity of monogenoidean parasites in Piaractus mesopotamicus farmed in cages in the reservoir of the Itaipu Hydroelectric Power Station, Paraná River, Brazil. The parasite distribution pattern and the correlation of prevalence and abundance with the total length of hosts were also investigated. Four monogenoidean species were collected: Anacanthorus penilabiatus, A. toledoensis, Mymarothecium ianwhitingtoni and M. viatorum. All the parasites collected in P. mesopotamicus showed the typical aggregated distribution pattern, and the abundance and the prevalence did not shown any correlation with the total length of hosts.
Parasitism by Monogenoidea in Piaractus mesopotamicus (Characiformes, Characidae) cultivated in Paraná river (Brazil)
Keywords: Anacanthorus; Monogenoidea; Mymarothecium; Paraná River; Piaractus mesopotamicus